Pandemic of the aging society — sporadic cerebral small vessel disease. Issue 2 (20th January 2021) - Lau, Alexander Yuk Lun; Ip, Bonaventure Yiu Ming; Ko, Ho; Lam, Bonnie Yin Ka; Shi, Lin; Ma, Karen Ka Yan; Au, Lisa Wing Chi; Soo, Yannie Oi Yan; Leung, Thomas Wai Hong; Wong, Adrian; Mok, Vincent Chung Tong
Abstract : Abstract: Age-related sporadic cerebral small vessel disease (CSVD) has gained increasing attention over the past decades because of its increasing prevalence associated with an aging population. The widespread application of and advances in brain magnetic resonance imaging in recent decades have significantly increased researchers' understanding in the in vivo evolution of CSVD, its impact upon the brain, its risk factors, and the mechanisms that explain the various clinical manifestation associated with sporadic CSVD. In this review, we aimed to provide an update on the pathophysiology, risk factors, biomarkers, and the determinants and spectrum of the clinical manifestation of sporadic CSVD.